Teachers’ written feedback: how to make it work more effectively in a language classroom? - Dung, Phung Thi Kim (H. : ĐHQGHN, 2020)
Teachers’ response to student writing is a vital, though neglected, aspect of second language composition research. This present study adds to previous research through the development and implementation of an original study which investigates the current feedback-giving practice of the teachers and their students’ opinions on feedback as well as their recommendations for improving it. The subjects involved in the study were 200 second-year students and 20 teachers at the University of Languages and International Studies (ULIS) under Vietnam National University, Hanoi (VNU) who are currently teaching or have taught writing before. These teachers and students were invited to join the survey, to answer the questionnaires, to participate in the interview, and to provide the source for observation. The research reveals that there exist a lot of problems concerning teachers’ responding methods, their feedback focus, their frequent types and forms of feedback as well as what they have actually done to help their students process feedback successfully. Meanwhile, the students report their opinions and preferences for more effective teachers’ feedback, which clearly reveals the mismatch between what the teachers often give and what the students would like to get. On this basis, the study recommends several important directions for teachers to utilize in improving their feedback, helping students process feedback more effectively and thus creating a condition in which learners learn to write more easily and successfully.